Determination of safe storage under controlled for rootstock seed of ‘Tahiti’ limes (2012)
One of the disadvantages in agricultural production is the adequate and timely supply of seeds. The absence of controlled storage methods of citrus seeds in nurseries is the main limiting factor for the production of planting material, because 40% of this material is lost through poor physiological quality of the seeds. The objective of this study was to determine the best conditions for storing seeds of CPB Citrumelo 4475 [Citrus paradise Macfad. × Poncirustrifoliata (L.) Raf.], Sunki × English [Citrus sunki Hort. ex Tan × Poncirus trifoliata (L.)Raf.] and ‘Volkameriana’ lemon (C. volkameriana Ten. And Pasq.), commonly used as rootstocks for ‘Tahiti’ limes (C.latifolia Tanaka). The seeds were packed in polyethylene bags and flasks with three levels of moisture on a fresh base: 10%-9%, 8%-7% and 6%-5%, under two storage conditions (10°C, 70% RH and 24°C, 80% RH) for 30, 90 and 180 days. The viability of the seeds was determined based on seed germination. Seeds from all evaluated plants reached a moisture level of 10%-9% after 3 days of drying at room temperature and levels of 8% to 7% and 6% to 5% after 2 hours and 14 hours when dried with silica gel. The highest germination values were between 0 and 30 days. The highest percentage of germination occurred with a moisture level of 10% and 9% for all tested citrus seeds. The experiment showed that the seeds from the three rootstocks had higher germination at an average temperature of 10°C with 70% RH. The type of packaging did not show significant differences.